Compliance in doing Senam Kesegaran Jasmani 1988 exercise improves cardiorespiratory endurance of attention deficit/hyperactivity disorder children (Faculty of Medicine Universitas Indonesia, 2018)
Background: Physical exercise was hypothesized to be able to improve the behavior of children with attention deficit/hyperactivity disorder (ADHD) by improving attention and concentration. Several studies mentioned that physical exercise could make ADHD children calmer, not only as a supportive therapy, but also as a therapeutic therapy. The aim of this study was to evaluate the effects of physical exercise to the behavior of ADHD patients and to analyze the effects of Senam Kesegaran Jasmani 1988 (SKJ 88) exercise compliance to the cardiorespiratory endurance in ADHD children.Methods: This study was an experimental study with 40 subjects from a special needs school in Tangerang, Indonesia. Subjects were given SKJ 88 exercise for 8 weeks, and the level of cardiorespiratory endurance was assessed with 600 m run before and after intervention.Results: 21 subjects (52.5%) were compliant, and the rest were very compliant. Although statistical analysis showed that there was no significant difference in cardiorespiratory endurance before and after intervention, the mean results of cardiorespiratory endurance test before intervention was higher than after. Mean time spent in the 600-m run before intervention was 497.9 seconds (SD 73.53), and after intervention was 313.7 seconds (SD 43.28).Conclusion: Based on the statistical test, we concluded that there was significant decrease of time spent for cardiorespiratory endurance test (p<0.001). The reduction of time taken to run 600 m by 184.3 seconds (SD 73.33) showed the improvement of cardiorespiratory endurance after the treatment.